Exogenous Hydrogen Sulfide Ameliorates Diabetic Myocardial Fibrosis by Inhibiting Cell Aging Through SIRT6/AMPK Autophagy - Yaling Li; Maojun Liu; Xiong Song; Xia Zheng; Jiali Yi; Da Liu; Sen Wang; Chun Chu; Jun Yang (Frontiers Media S.A., 2020)
Stress aging of myocardial cells participates in the mechanism of myocardial fibrosis (MF). Previous studies have shown that hydrogen sulfide (H2S) can improve MF, however the specific internal mechanism remains still unclear. Therefore, this study aims to explore whether H2S can improve myocardial cell aging induced by high glucose and myocardial fibrosis in diabetic rats by activating autophagy through SIRT6/AMPK. We observed that HG (high glucose, 33 mM) induced down-regulation of endogenous H2S-producing enzyme CSE protein expression, increased cell senescence, down-regulation of autophagy-related proteins Beclin1, Atg5, Atg12, Atg16L1, and inhibition of SIRT6/AMPK signaling pathway in H9c2 cardiomyocytes. H2S (NaHS: 400 μM) could up-regulate CSE protein expression, inhibit cell senescence, activate autophagy and SIRT6/AMPK signaling pathway. On the contrary, no above phenomena was achieved upon addition of CSE inhibitor PAG (dl-propargylglycine: mmol/L). In order to further elucidate the relationship between H2S and SIRT6/AMPK signaling pathway, dorsomorphin dihydrochloride (Dor), an inhibitor of AMPK signaling pathway, was added to observe the reversal of H2S's inhibitory effect on myocardial cell aging. At the same, streptozotocin (STZ; 40 mg/kg) was injected intraperitoneally to build an animal model of diabetic SD rats. The results showed that myocardial collagen fibers were significantly deposited, myocardial tissue senescent cells were significantly increased and the expression of CSE protein was down-regulated, while SIRT6/AMPK signaling pathway and cell autophagy were significantly inhibited. H2S-treated (NaHS; 56 μmol/kg) could significantly reverse the above phenomenon. In conclusion, these findings suggest that exogenous H2S can inhibit myocardial cell senescence and improve diabetic myocardial fibrosis by activating CSE and autophagy through SIRT6/AMPK signaling pathway.